TRANSFORMATION OF FISHERMEN'S CULTURE POST RECLAMATION OF PT. BTID IN SERANGAN, DENPASAR - Segara, I Nyoman Yoga (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Serangan island fishermen were known as great sailors. They sailed outside Bali and were known as fresh fish producers. They could produce fresh fish only around the island. The catch, usually sold by women in traditional markets and door to door. But since PT. BTID conducted reclamation in the 1990s, the life of Serangan fishermen was not like its heyday. Fish-seeking areas are narrow because of damage to marine ecosystem. Even parking the boat has been limited because some beaches previously owned by Serangan people now belong to PT. BTID is not permitted to enter. As a result, they parked boats anywhere and are now looking for fish around Sanur or Nusa Dua. The sea is no longer the main source of life. Many young people are no longer fishermen, their parents switch professions, become parking and security guards, and sell seaweed and shellfish. But the new profession does not guarantee their lives. Cultural transformation is being experienced by fishermen, to change their perspective of sea. Making Serangan as a departure dock for tourists to Lembongan or Lombok and Turtle Park as a tourist icon are some of the results of cultural transformation in the lives of Serangan community.